Developing a European Psychotherapy Consortium (EPoC): Towards Adopting a Single-Item Self-Report Outcome Measure Across European Countries - Miguel M. Gonçalves; Wolfgang Lutz; Brian Schwartz; João Tiago Oliveira; Suoma E. Saarni; Orya Tishby; Julian A. Rubel; Jan R. Boehnke; Adrian Montesano; Dario Paiva; Davide Ceridono; Emmanuelle Zech; et al. (Clinical Psychology in Europe)
[Background] Complementing the development of evidence-based psychological therapies, practice-based evidence has developed from patient samples collected in routine care, addressing questions relevant to patients and practitioners, and thereby expanding our knowledge of psychological therapies and their impact. Implementation of assessments in routine care allows for timely clinical decision support and the collection of multiple practice-based data sets by addressing the needs of patients and clinicians (e.g., routine outcome monitoring) and the needs of researchers (e.g., identifying the impact of therapist variables on outcomes). [Method] In this article we describe an initiative developed in Europe, through the European Chapter of the Society for Psychotherapy Research, aimed at creating a consortium that has the potential for collecting data on tens of thousands of patients per year. [Results] A survey identified one of the main problems in the development of a common data set to be the heterogeneity of measures used by members (e.g., 87 different pre-post outcomes). We report on the results of the survey and the initial stage of identifying a single-item – the Emotional and Psychological Outcome (EPO-1) – measure and the process of its translation into multiple European languages. [Conclusions] We conclude this first stage of the overall project by discussing the future potential of the Consortium in relation to the development of procedures that allow crosswalks of outcome measures and the creation of a task force that may be consulted when new data sets are collected, aiming for new common measures to be implemented and shared.